Relationship Between Benign Prostatic Hyperplasia and Metabolic Syndrome - Taufiq Nur Budaya; Ardian Rizal; Hafizh Ananda Wibowo; Fauzan Kurniawan Dhani (Brawijaya Journal of Urology, 2024)
Introduction. Benign Prostatic Hyperplasia (BPH) is a medical condition where there is an excessive growth of smooth muscle and epithelial cells in the prostate gland. BPH is typically seen in older men and is non-cancerous. It is estimated that around 50% of men aged 60 or above worldwide are affected by BPH. Some research has looked into the factors that may increase the risk of BPH, and one theory suggests a possible connection between metabolic syndrome and the development of BPH. This study aims to investigate the potential relationship between metabolic syndrome and the development of BPH.Methods. This study is an analytical observational research conducted at Saiful Anwar Hospital in Malang from 2015 to 2020, employing a case-control research design. The data used for this study are secondary data extracted from medical records. The data analysis involved the application of both Chi-Square and Logistic Regression methods.Results. The study gathered data from 90 patients, and the analysis revealed that the highest number of BPH patients fell into the category of those with hypertension, totaling 34 individuals (75.56%). Among the factors considered, including fasting blood glucose, body mass index, and metabolic syndrome, the chi-square test indicated that body mass index and blood pressure were significantly associated with BPH, both yielding p-values of 0.046; OR (95%Cl) = 2.473 (1.006 – 6.075). Furthermore, in the logistic regression test, it was determined that fasting blood glucose, blood pressure, and body mass index categories had a significant impact on BPH.Conclusions. This research illustrates that there is an association between type 2 diabetes, hypertension, and obesity with the occurrence of BPH. However, there is no statistically significant relationship between the components of metabolic syndrome and the occurrence of BPH.